2014
DOI: 10.1186/2046-4053-3-29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drug reminder packaging on medication adherence: a systematic review revealing research gaps

Abstract: BackgroundThis was a systematic review of the literature in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Evidence mapping was used to reveal the effect of drug reminder packaging on medication adherence, to identify research gaps and to make suggestions for future research.MethodsPubMed, Embase, CINAHL and PsycINFO were searched with an end date of September 2013 using the Medical Subject Headings (MeSH) term ‘medication adherence’ and 20 different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 62 publications
1
40
0
Order By: Relevance
“…One possible reason for this is that blister packs provide a visual aid for patients who may struggle to remember to take their medications. [18][19][20] Additionally, they continued to see a gradual improvement in their proportion of days covered (PDC) scores, such that the average PDC score for this group was 0.90 at 12 months. Patients who were receiving MTM services saw improvements in their clinical outcomes in comparison to the patients in the pill bottle (PB) only group.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One possible reason for this is that blister packs provide a visual aid for patients who may struggle to remember to take their medications. [18][19][20] Additionally, they continued to see a gradual improvement in their proportion of days covered (PDC) scores, such that the average PDC score for this group was 0.90 at 12 months. Patients who were receiving MTM services saw improvements in their clinical outcomes in comparison to the patients in the pill bottle (PB) only group.…”
Section: Discussionmentioning
confidence: 95%
“…Dispensing medications in blister packaging rather than pill bottles has been shown to improve adherence and clinical outcomes. [18][19][20] This can replace pill boxes that patients or caregivers typically fill after receiving their prescriptions in pill bottles. 17 To reduce multiple trips to the pharmacy, pharmacies are able to synchronize patients' medications to be filled on one day.…”
Section: Introductionmentioning
confidence: 99%
“…Foreseeably, there will be a marked increase in the number of very old people living alone, so that work on helping them to reduce the risks of home medication could become a priority in the area of patient safety. As occurs in the professional context, aids and tools that could be incorporated for reducing the likelihood of MEs constitute one of the core aspects in efforts to increase patient safety, and in this area the new technologies (we can cite two examples: e-prescriptions and medication-related apps) can contribute to greater security in the use of medicines, as already seems to be the case [102].…”
Section: Expert Opinionmentioning
confidence: 99%
“…A systematic review, published in 2014, identified 30 studies (5737 participants) on the use of drug reminder packaging 9. Ten were randomised controlled trials, 19 controlled clinical trials and one was a cohort study.…”
Section: What Is the Evidence Of Benefit?mentioning
confidence: 99%